Adolescent motivation to attend youth programs: A mixed-methods investigation. Issue 4 (1st October 2016) - Akiva, Thomas; Horner, Christy Galletta
ABSTRACT: Research suggests that adolescents can benefit from participating in youth programs; however, recruitment and retention are challenging for many programs, and youth living in low-income, urban areas can be the hardest to reach. We investigated motivation to attend a neighborhood-based program for urban adolescents. Participants completed questionnaires ( N = 141, M age = 16.6, 88% African American), and a subsample ( n = 34) also participated in face-to-face interviews. Findings suggest that although content is the primary surface driver of attendance for most youth, a large majority of youth would choose to retain staff and peers over content, and that staff and content reasons are intertwined. Attending for peer reasons was negatively associated with attendance frequency. Cluster analysis suggested five patterns of reasons for continued participation, which were related to overall program motivation and attendance frequency. Implications for programs include focusing on providing quality content while recognizing the importance of strong youth-staff relationships.